EVALUATION OF THE FUNDAMENTAL MOTOR SKILLS IN CHILDREN 10 TO 12 YEARS: A COMPARATIVE STUDY (Fiep Bulletin - online, 2012)
The lack of activities that require coordination and motor skills usually entails decreased motor performance, and these are intertwined with embezzlement amount of motor experiences lived. Taking into account that the practice is the key to the development of standards for maximum motor skills, children will refine their motor skills in physical education classes at school. This study aimed to analyze and compare the levels of motor skills of 47 children aged 10 to 12 years in a public school in the city of  in relation to 47 children of similar age in a public school in the city of Marechal Deodoro. This was a descriptive and comparative, using tests based on analytical matrix of fundamental motor skills Gallahue (2005). The results indicated significant differences between groups of schools in the cities of Maceio and Marechal Deodoro, showing that recruited children still had low frequencies in the mature stage of the classification of fundamental motor skills despite students have available regular physical education classes in school. Making a real need for physical education classes to meet the broader needs of children motor stimulation.
Keywords: fundamental movement skills; physical education; assessment of fundamental motor skills.